Gravid oviposition sticky trap and dengue non-structural 1 antigen test for early surveillance of dengue in multi-storey dwellings: study protocol of a cluster randomized controlled trial - Jonathan Wee Kent Liew; Sivaneswari Selvarajoo; Wing Tan; Rafdzah Ahmad Zaki; Indra Vythilingam (BMC, 2019)
Abstract Background Dengue is a global disease, transmitted by the Aedes vectors. In 2018, there were 80 615 dengue cases with 147 deaths in Malaysia. Currently, the nationwide surveillance programs are dependent on Aedes larval surveys and notifications of lab-confirmed human infections. The existing, reactive programs appear to lack sensitivity and proactivity. More efficient dengue vector surveillance/control methods are needed. Methods A parallel, cluster, randomized controlled, interventional trial is being conducted for 18 months in Damansara Damai, Selangor, Malaysia, to determine the efficacy of using gravid oviposition sticky (GOS) trap and dengue non-structural 1 (NS1) antigen test for early surveillance of dengue among Aedes mosquitoes to reduce dengue outbreaks. Eight residential apartments were randomly assigned into intervention and control arms. GOS traps are set at the apartments to collect Aedes weekly, following which dengue NS1 antigen is detected in these mosquitoes. When a dengue-positive mosquito is detected, the community will be advised to execute vector search-and-destroy and protective measures. The primary outcome concerns the the percentage change in the (i) number of dengue cases and (ii) durations of dengue outbreaks. Whereas other outcome measures include the change in density threshold of Aedes and changes in dengue-related knowledge, attitude and practice among cluster inhabitants. Discussion This is a proactive and early dengue surveillance in the mosquito vector that does not rely on notification of dengue cases. Surveillance using the GOS traps should be able to efficiently provide sufficient coverage for multistorey dwellings where population per unit area is likely to be higher. Furthermore, trapping dengue-infected mosquitoes using the GOS trap, helps to halt the dengue transmission carried by the mosquito. It is envisaged that the results of this randomized controlled trial will provide a new proactive, cheap and targeted surveillance tool for the prevention and control of dengue outbreaks. Trial registration This is a parallel-cluster, randomized controlled, interventional trial, registered at ClinicalTrials.gov (ID: NCT03799237), on 8th January 2019 (retrospectively registered).